Network Efficiency Amendment Utilizing Cloud Radio Access Network In Mobile Communications - P, Karthikala.; C.Arunachala Perumal, Dr.; M.Ramya, Ms. (International Journal of Engineering and Technology, 2018)
Mobile data traffic is finding exponential growth currently in telecommunications industry. It has become important to concentrate on both spectral and energy efficiencies in utilizing cellular networks under green communication standpoint. Thus, for 5G the utmost priority is that to increase data traffic and reduce the total network energy ingesting by half. The proposed work is to design the Cloud Radio Access Network (C-RAN) with energy efficient, flexible and capacity-enhanced features by effectively bundling and establishing relation between BBU and RRU utilizing Catechistic technique. Mathematical results with realistic parameters prove that the projected optimization design clearly improve the energy efficiency of C-RANâ€™s compared to standard schemes. Â